Beyond Cruelty. A Frightening Friend of Terrifying Psychoanalysis - VLAISAVLJEVIĆ, Ugo (Anafora, 2023)
The article proposes a close reading of Jacques Derrida’s address to the Estates General of Psychoanalysis, held in Paris in July 2000. In celebrating the centenary of Freud’s Interpretation of Dreams, the representative international gathering of psychoanalysts took place under the umbrella of a “political metaphor” suggested by its historically significant title and dates. In Derrida’s address, the metaphor of revolution was far more than just a bright emblem of the meeting, expressing the organizers’ wish to emphasize the revolutionary character of Freud’s “invention” or to encourage the participants’ en- thusiasm for solving the current crisis of their profession in the manner inspired by the Estates General in 1789. It is only in his late work, and particularly in this introductory lecture dealing with human cruelty and its recent historical mutations, that Derrida began to explore the deconstructive political potentialities of psychoanalysis. His hypothesis on the superiority of psychoanalysis over all other discourses in dealing with this highly political issue assumes that there is, although not yet fully recognized, or even strongly opposed, a politics inherent to Freud’s theory. Outlined in his later writings, Freud’s “progressive politics,” already engaged in a subversion of the principle of state sovereignty, as proved to be able to indicate a strategy of going “beyond the death drive,” calls for creating a new, revolutionary psychoanalysis beyond all principles. The article attempts to reveal that Derrida’s politically oriented reading of Freud’s legacy crucially depends on his unique position of “the friend of psychoanalysis.”